Islamic human geography - making space for a conversation of difference - Amriah Buang, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2013)
Whether acknowledged by the West or not an Islamic epistemology exists for both natural and human sciences. And since advancing postcolonial geography must also include the decolonization of knowledge, it is timely to consider if an alternate, Islamic human geography has instructive worth with respect to mainstream human geography. This paper sketches a broad outline of an Islamic human geography and shows how it (i) addresses some of the fundamental epistemological questions non-Islamic, largely secularised, geographies of the West have abandoned or silenced; (ii) incorporates a number of ideas within mainstream human geography; and (iii) outlines novel frameworks for synthesizing differences that trouble mainstream human geography. While the showcasing of Islamic geography may not alter its irrelevance to secular and non-Islamic geographies its illumination confirms its relevance to Muslim contexts and, by refraction, the situated nature of mainstream human geography. As such, this exploration serves the purpose of opening out the kind of conversation across difference that post-colonialism seeks to advance.